Les réfugiés dans le monde entre protection et illégalité - Olivier Clochard (EchoGéo, 2008)
Spatial distributions of interns’ displacement people (IDP) and refugees in the World underline that the developed countries receive a low number of this people. There is a strong demographic imbalance between States such today Syria, Chad or Sudan and countries developed where the applicants are relatively very few. In addition, the refugees theoretically protected by the convention of Geneva from 1951, are considered more and more by the European States, like migrants illegal and treated like such.